1991
DOI: 10.1161/01.hyp.18.4_suppl.ii60
|View full text |Cite
|
Sign up to set email alerts
|

Role of angiotensin II in injury-induced neointima formation in rats.

Abstract: Angiotensin converting enzyme inhibition markedly suppresses neointima formation in response to balloon catheter-induced vascular injury of the rat carotid artery. To determine whether this effect was mediated through the vasoactive peptide angiotensin II (Ang II), two approaches were followed. First, the balloon model was used to compare the effects of continuous infusion of Ang II, with and without concurrent converting enzyme inhibition by cilazapril; second, the effects of the orally active nonpeptidic Ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(51 citation statements)
references
References 0 publications
1
50
0
Order By: Relevance
“…In vivo studies have reported that Ang II infusion induces marked intimal smooth muscle cell proliferation in rat carotid arteries [17,21], and that ACE inhibitors suppress myointimal proliferation after vascular injury [14,18]. Intimal thickening can also be prevented by Ang II receptor type-1 antagonists [66]. However, all these effects are probably also related to an action on bradykinin metabolism [67].…”
Section: Atherosclerosis and Restenosismentioning
confidence: 99%
“…In vivo studies have reported that Ang II infusion induces marked intimal smooth muscle cell proliferation in rat carotid arteries [17,21], and that ACE inhibitors suppress myointimal proliferation after vascular injury [14,18]. Intimal thickening can also be prevented by Ang II receptor type-1 antagonists [66]. However, all these effects are probably also related to an action on bradykinin metabolism [67].…”
Section: Atherosclerosis and Restenosismentioning
confidence: 99%
“…14 Another enzyme present in mast cells is the metalloprotease, carboxypeptidase A enzyme. This enzyme cleaves the His 9 -Leu 10 bond in angiotensin I and as a result generates the fragment angiotensin [1][2][3][4][5][6][7][8][9] , which although capable of inhibiting ACE, has no known intrinsic contractile activity. 26 The human heart has been shown to possess carboxypeptidase A activity, generation of angiotensin [1][2][3][4][5][6][7][8][9] by this enzyme is sufficient to block cardiac ACE.…”
Section: Alternative Angiotensin II Generating Enzymesmentioning
confidence: 99%
“…This enzyme cleaves the His 9 -Leu 10 bond in angiotensin I and as a result generates the fragment angiotensin [1][2][3][4][5][6][7][8][9] , which although capable of inhibiting ACE, has no known intrinsic contractile activity. 26 The human heart has been shown to possess carboxypeptidase A activity, generation of angiotensin [1][2][3][4][5][6][7][8][9] by this enzyme is sufficient to block cardiac ACE. 27 It is undetermined if human blood vessels also exhibit cardoxypeptidase A activity, or if endogenous local ACE activity in the vessel wall is regulated by the synthesis of angiotensin [1][2][3][4][5][6][7][8][9] .…”
Section: Alternative Angiotensin II Generating Enzymesmentioning
confidence: 99%
See 2 more Smart Citations